Sonates pour le Piano-forte composées par Louis van Beethoven. No. [5]. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; H. Böie; Altona, 2022)
Mid-nineteenth century edition of the Piano Sonata no. 8 in C minor, op. 13, published by H. Böie in Altona as no. 5 of the collection "Sonatas pour le piano-forte composées par Louis van Beethoven."